Miniaturized Filters with a Controllable Number of Passbands by Embedding Serpentine Microstrip Resonators in SIW - Xiaohei Yan; Wenjing Mu; Minjie Guo (International Journal of Antennas and Propagation)
This study proposes a novel simple structure based on evanescent-mode theory for the design of miniaturized filters with good out-of-band rejection and controllable passband number characteristics. The filter structure is realized by embedding serpentine microstrip resonators in the upper metal surface of the substrate-integrated waveguide (SIW). These resonators are composed of upper and lower parts, which form a single-passband filter when the lengths are equal and a double-passband filter when the lengths are unequal. This paper proposes a novel method for switching between single- and dual-passband configurations by modifying the length of the serpentine microstrip resonators without altering the overall SIW dimensions. Furthermore, finite transmission zeros are incorporated into the filter to augment the out-of-band rejection capability of the filter and the isolation effect between the passbands of the dual-passband filter. To ascertain the viability of the proposed design, a two-stage single-passband filter and a two-stage dual-passband filter were fabricated and tested in this study. The experimental results align closely with the simulation outcomes, effectively validating the efficacy of this design.